Sustainable Water Resources Management through Disaggregated Multi-Region Virtual Water Flow and Interaction Analysis - Boyue Zheng; Lirong Liu; Guohe Huang; Brian Baetz; Mengyu Zhai; Kaiqiang Zhang; Chen Lu (Water Resources Management, 2024)
Virtual water transfer is considered as an important pathway to alleviate water shortage in arid regions due to limited water resources and unbalanced distribution. It is essential to explore the hidden mechanism of virtual water transfers among multiple regions to support future water resources allocation and management. In this study, a Disaggregated Multi-Region Virtual Water Flow and Interaction (DrWIn) model is developed to facilitate the analysis of virtual water inflow, outflow, transfer balance, and the related interactions. In addition, a factorial analysis is integrated to quantify the impacts of industrial water consumption and their interactive effects. A special case study of China is conducted to illustrate the applicability and superiority of the DrWIn model. It is found that interaction effects of any two industries are negative, indicating that high freshwater consumption in two industries is not the best choice. The obtained results provide a solid scientific basis for identifying the key industries and regions across a multi-region study system and supporting water resources utilization management in the future.